Ethical Conciliation Hearings held by the Regional Nursing Council of São Paulo - Vagner Urias; Vinicius Gomes Barros; Marcelo José dos Santos (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the Ethical Conciliation Hearings held by the Regional Nursing Council of São Paulo. Methods: this is a retrospective study, of a quantitative approach, with documentary analysis. To obtain the data, documents related to ethical processes were analyzed. The time frame established for the study was from January 1, 2011 to December 31, 2017. Results: 513 Ethical Conciliation Hearings were held and ratified. Nurses represent the category that most denunciate and are most accused. The highest percentages of ethical conciliations were in events related to public and hospital institutions. The Conduct Adjustment Term was the modality with the highest number of agreements. The main reason of conciliation failure was the non-attendance of at least one of the parties. Conclusions: the Ethical Conciliation Hearings represent an effective alternative instrument for the resolution of ethical-disciplinary processes in nursing.